MENINGKATKAN KEMANDIRIAN ANAK DENGAN MENGGUNAKAN MODEL PEMBELAJARAN DI LUAR KELAS DI KB DHARMA MULYA TENGGARONG SEBERANG TAHUN PELAJARAN 2016/2017 - Tutik - Tutik; Harry - Gunawan (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
Concerning with the low level of autonomy on students of Class A in Dharma Mulya Playgroup Tenggarong, the researcher aims to investigate the effectiveness of outdoor education in improving students’ independence, by conducting a classroom action research. The researcher applied two cycles, which in each cycle, consisting of planning, implementation, observation and reflection. Observation and documentation were employed in terms of data collection. Meanwhile, percentage analysis was carried out as data analysis. Moreover, as the research subjects, the researcher involved 30 students. At the first cycle, during three meetings, students’ autonomy increased 59.4%. Likewise, the percentage of students who successfully improved their autonomy inclined into 85.4%. Having compared the percentage of students’ autonomy in cycle 1 and cycle 2, students’ had positivelyenhanced their autonomy for 25% in cycle 2. Therefore, it can be concluded that the outdoor education has effectively increased students’ autonomy in Class A of Dharma Mulya Playgroup Tenggarong. Subsequently, it is suggested for teachers to apply outdoor education as the alternative learning method which can increase students’ self-sufficiency from 59.4% into 85.4%.